Sprinting technique and foot contact. Are you putting on the brakes? (Coaching Track & Field Athletics)
In sprinting technique one of the common issues that the author sees is the lack of correct foot positions when the foot contacts the ground. This seems to be, in his experience, one of the main areas that coaches neglect.